Pertambahan koleksi dan pengurusan ruang secara berkesan : Pengalaman Perpustakaan UKM - Umar, Rohaya; Maidin, Abu Bakar (Persatuan Pustakawan Malaysia, 2012)
Generally, every year a library’s collection will increase in tandem with the university’s current reference needs in education and research. An increase in collection will result in an increase in the need for space which will result in a decrease of users’ space. Therefore, the space in a library has to be managed effectively to meet the users’ current needs. This paper looks at the current status of space allocation in Malaysian public university libraries. It presents the experiences and strategies adopted by the UKM Library in effectively managing use of space. This includes the establishment of a 24-hour reading area and a Weeding Collection.